Lipid microdomains and the regulation of ion channel function - Dart, Caroline (Blackwell Science Inc, 2010)
Many types of ion channel localize to cholesterol and sphingolipid-enriched regions of the plasma membrane known as lipid microdomains or ‘rafts’. The precise physiological role of these unique lipid microenvironments remains elusive due largely to difficulties associated with studying these potentially extremely small and dynamic domains. Nevertheless, increasing evidence suggests that membrane rafts regulate channel function in a number of different ways. Raft-enriched lipids such as cholesterol and sphingolipids exert effects on channel activity either through direct protein–lipid interactions or by influencing the physical properties of the bilayer. Rafts also appear to selectively recruit interacting signalling molecules to generate subcellular compartments that may be important for efficient and selective signal transduction. Direct interaction with raft-associated scaffold proteins such as caveolin can also influence channel function by altering gating kinetics or by affecting trafficking and surface expression. Selective association of ion channels with specific lipid microenvironments within the membrane is thus likely to be an important and fundamental regulatory aspect of channel physiology. This brief review highlights some of the existing evidence for raft modulation of channel function.